2016
DOI: 10.1088/1674-1056/25/6/067502
|View full text |Cite
|
Sign up to set email alerts
|

Electrical control of magnetism in oxides

Abstract: This review article aims at illustrating the recent progresses in the electrical control of magnetism in oxides with profound physics and enormous potential applications. In the first part, we provide a comprehensive summary of the electrical control of magnetism in the classic multiferroic heterostructures and clarify their various mechanisms lying behind. The second part focuses on the novel route of electric double layer gating for driving a significantly electronic phase transition in magnetic oxides by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 159 publications
(379 reference statements)
1
27
0
Order By: Relevance
“…The accumulated opposite charges form an electric double layer with ≈3 nm thickness . Consequently, the surface charge density n s dramatically achieves 10 15 cm −2 and can further lead to a strong interfacial E‐field . Figure is the resulting interesting interfacial phenomena.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulated opposite charges form an electric double layer with ≈3 nm thickness . Consequently, the surface charge density n s dramatically achieves 10 15 cm −2 and can further lead to a strong interfacial E‐field . Figure is the resulting interesting interfacial phenomena.…”
mentioning
confidence: 99%
“…The electrochemical windows for both Kapton and mica have been calibrated in Figure S2 (Supporting Information). We chose V g (4 V for Kapton, 3 V for mica) out of the electrochemical window because larger bias voltage has a larger charge density, which can be more effective for the modulation of RKKY interaction. Since the situation in electrochemical reaction region is rather complicated, we only considered positive V g as a simplification.…”
mentioning
confidence: 99%
“…The RF (Radio Frequency)/microwave ME tunability (≈60 Oe), however, is limited in BFO systems . Furthermore, there are many reports on magnetism control using the interfacial charge effect in dielectric/magnetic heterostructures . Magnetic moment as well as surface magnetic anisotropy is effectively controlled by interfacial charge that fills the 3d orbital of magnetic ions at the interface .…”
mentioning
confidence: 99%
“…In 2007, Weisheit et al first reported E‐field driven coercive field ( H c ) changes in (FePt or FePd)/electrolyte heterostructures with liquid gating, which proved the concept of E‐field stimulated carrier‐mediated ME coupling phenomenon . Further, the ionic‐liquid (IL) gating process under low V g (usually <3 V) has been investigated using a typical field‐effect transistor (FET) structure (see Figure a), which can be utilized in the E‐field driven magnetism.…”
mentioning
confidence: 99%
See 1 more Smart Citation